Effectiveness of Group Counseling Services in Increasing Social Interaction in Students: Literature Review - Okti, Diana Rezu (JUPE : Jurnal Pendidikan Mandala, 2024)
Social interaction is basically an individual relationship between individuals, or individuals and groups that mutually influence, change, improve behavior in living together. If social interaction is established well then this will be beneficial for the teenagers themselves. This article aims to determine the effectiveness of group counseling services in increasing students' social interactions in junior high schools. The research method used in this review is a literature review. Literature review is a term to refer to a particular study or research and development carried out to collect and evaluate research related to a particular topic focus. Social interaction is an important thing that every individual must have, therefore the results obtained are good social interaction, good socialization skills are also needed and improving social interaction can be done by conducting group counseling. Group counseling plays a significant role in the development of student communication, students who initially have limitations in communicating and interacting socially and tend to become isolated after attending group counseling tend to be more able to interact well with life social.